Phytoplankton dynamics in a coastal saline lake (SE-Portugal) - Morais, P. (2012)
The aim of this study was to characterise phytoplankton dynamics in a coastal saline lake, pinpointing putative biotic and abiotic regulatory variables of its succession and productivity. Between February and September 1998, samples for the analysis of physical, chemical and biological variables were taken fortnightly (except in February and April). The phytoplankton community showed three distinct periods of evolution. The first period (February-March) was characterised by a chroococoid non-colonial cyanobacteria bloom (maximum abundance, 4.3 × 109cells l–1) and also by its decaying. Long water residence and/or nitrogen limitation might have allowed cyanobacteria dominance; while its decaying could be associated to predation by aplastidic nanoflagellates and/or to the beginning of periodical partial renewal of lake water with water proceeding from an adjacent coastal lagoon (Ria Formosa). The second period (April-early August) can be differentiated, from the previous, by reduced abundances of phytoplankton (minimum abundance, 5.7 × 106 cells l–1) and plastidic nanoflagellates dominance. The overall low nutrient concentrations, likely as a consequence of periodical partial water renewal, could explain these results. In the last period (late August-September), increased phytoplankton abundance and the development of a diatom and mixotrophic dinoflagellate bloom was probably the result of a sudden increase in nutrient levels, occurring after a period of intense precipitation. In consequence, primary production reached a maximum value of 1367 mg C m–3 h–1; 36 times higher than a maximum value previously reported for Ria Formosa.